International collaboration for pest management: On stopping an invasive pest of stored maize - International Maize and Wheat Improvement Center (International Maize and Wheat Improvement Center, 2023)
Hannah Quellhorst completed a B.S. and M.S. in Entomology at Purdue University. She recently completed a Ph.D. in Stored Products Entomology at Kansas State University, co-advised by Drs. Rob Morrison (USDA-ARS) and Kun-Yan Zhu (KSU). Her research focuses on improving the management of maize both domestically (USA) and internationally. Her interests include global food security, international development, women empowerment, insect biochemistry and physiology, and insect behavior. In the future, she hopes to focus on humanitarian science through a career in Entomology. Ultimately, she hopes to apply her skills to fight world hunger.